2016
DOI: 10.1074/jbc.m116.743443
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal Ankyrin Repeat Domain Is Not Required for Electrophile and Heat Activation of the Purified Mosquito TRPA1 Receptor

Abstract: Temperature sensors are crucial for animals to optimize living conditions. The temperature response of the ion channel transient receptor potential A1 (TRPA1) is intriguing; some orthologs have been reported to be activated by cold and others by heat, but the molecular mechanisms responsible for its activation remain elusive. Single-channel electrophysiological recordings of heterologously expressed and purified Anopheles gambiae TRPA1 (AgTRPA1), with and without the N-terminal ankyrin repeat domain, demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 51 publications
(109 reference statements)
2
32
1
Order By: Relevance
“…Previous studies have shown that species differences between a small number of residues in the transmembrane core give rise to capsaicin sensitivity in TRPV1 and icilin sensitivity in TRPM8 (19,25). Additionally, the transmembrane domain of TRPA1 is sufficient to recapitulate temperature and agonist response of this channel (46,47). Given the importance of the transmembrane core in TRP channel function, we focused our search on this region.…”
Section: Species-dependent Modulation Of Trpm8 By Pirtmentioning
confidence: 99%
“…Previous studies have shown that species differences between a small number of residues in the transmembrane core give rise to capsaicin sensitivity in TRPV1 and icilin sensitivity in TRPM8 (19,25). Additionally, the transmembrane domain of TRPA1 is sufficient to recapitulate temperature and agonist response of this channel (46,47). Given the importance of the transmembrane core in TRP channel function, we focused our search on this region.…”
Section: Species-dependent Modulation Of Trpm8 By Pirtmentioning
confidence: 99%
“…Presumptive IR coreceptors (IRco-y) are required for the reception of multiple chemical classes in multiple cell types ( Abuin et al, 2011 ; Pitts et al, 2017 ), but their exact role in signal transduction remains elusive. Transient Receptor Potential (TRP) channels assemble as homotetramers ( Survery et al, 2016 ) sensitive to electrophiles (allyl isothiocyanate shown as example). These multimodal channels are approximately three times as large as ORs and GRs.…”
Section: Primary Receptor Familiesmentioning
confidence: 99%
“…Together, these findings support the notion that Ag TRPA1 functions as a peripheral thermoreceptor in mosquito antenna. More recent work has uncovered an additional chemosensory role for Ag TRPA1 ( Survery et al, 2016 ). Patch clamp recordings on heterologously expressed and purified, full-length Ag TRPA1 and truncated Δ1–776 Ag TRPA1 (lacking the N-terminal ARD) demonstrated that both proteins are functional, as each responded to the electrophilic compounds, allyl isothiocyanate and cinnamaldehyde, as well as heat.…”
Section: Ancillary Membrane Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, selective blockers are added to confirm that currents are due to activity of a reconstituted channel. It is reported that reconstituted TRPA1 is blocked by non‐selective TRP channel pore blocker ruthenium red (Moparthi et al., ; Survery et al., ) as well as by the selective TRPA1 antagonist HC030031 (Moparthi et al., ) in the Port‐a‐Patch system.…”
Section: Commentarymentioning
confidence: 99%